A relação entre inovação, mercado acionário e crescimento econômico - Dalle Nogare, Gelson Eduardo (2015)
The relationship between financial systems and economic growth has not been well assimilated by the academic community and the public managers, generating debates inconclusive for many decades. However, the center of this debate lies the question of whether the financial sector responsible for the development of the economic sector for real, or is the real sector that drives the evolution and development of the financial sector. This relationship becomes even more complex when trying to analyze the relationship and the intrinsic role of innovation as a mechanism driver of stock market performance and hence the real economy. Thus, the stock market can be a predictor of evolution of economic growth and technological innovation and serve as an economic indicator? The objective of this study was to analyze the behavior and the relationship of the stock market with macroeconomic developments, based on technology development through the variables that influence these indexes for Brazil, Russia, India, China and South Africa - the BRICS. Thus, the theoretical foundation was made through research in books, scientific articles and justified by the hypothesis that a decrease in stock prices may reflect bad news in relation to technological progress and long-term economic growth. Was set as a reference for Question innovation, the target provided by The Global Innovation Index (GII) for Question economic growth was used as reference real GDP and for the requirement of the capital market, it used the main stock index of each country's stock exchange. To analyze and relate these variables made use of the correlation coefficient calculation and leaned on the scatter diagram. The results suggest that the study hypothesis was rejected in a systematic way and concluded that the performance of the capital market can not serve as an economic indicator, because it is not found evidence of their performance related to the performance of the real economy and technological innovation.